A massive cluster at z = 0.288 caught in the process of formation: The case of Abell 959. Issue 4 (28th May 2019) - Bîrzan, L; Rafferty, D A; Cassano, R; Brunetti, G; van Weeren, R J; Brüggen, M; Intema, H T; de Gasperin, F; Andrade-Santos, F; Botteon, A; Röttgering, H J A; Shimwell, T W
ABSTRACT: The largest galaxy clusters are observed still to be forming through major cluster–cluster mergers, often showing observational signatures such as radio relics and giant radio haloes. Using LOFAR Two-meter Sky Survey data, we present new detections of both a radio halo (with a spectral index ofα _143^1400=1.48^+0.06_-0.23 ) and a likely radio relic in Abell 959, a massive cluster at a redshift of z = 0.288. Using a sample of clusters with giant radio haloes from the literature (80 in total), we show that the radio halo in A959 lies reasonably well on the scaling relations between the thermal and non-thermal power of the system. Additionally, we find evidence that steep-spectrum haloes tend to reside in clusters with high X-ray luminosities relative to those expected from cluster luminosity–mass ( LM ) scaling relations, indicating that such systems may preferentially lie at an earlier stage of the merger, consistent with the theory that some steep-spectrum haloes result from low-turbulence mergers. Lastly, we find that halo systems containing radio relics tend to lie at lower X-ray luminosities, relative to those expected from cluster LM scaling relations, for a given halo radio power than those without relics, suggesting that the presence of relics indicates a later stage of the merger, in line with simulations.